Young Jazz Musicians and Negotiation of Public Space in Yogyakarta Indonesia - Sutopo, Oki Rahadianto (Universitas Negeri Semarang, 2017)
Using Bourdieusian approach, this article explores the reflexive strategies of young jazz musicians in order to develop their musical practices in a contemporary urban context of Yogyakarta, a city of culture and activism in Indonesia. In detail, the reflexive strategy (Sweetman 2003; Threadgold & Nilan 2009) will be explained as the manifestation of struggle in the field of cultural production (Bourdieu 1993). As an implication, young jazz musicians have to negotiate their musical practices with the reproduction of doxa and the representation of dominant agents in the jazz music field including the availability of public spaces in contemporary Yogyakarta. The resistance towards doxa will be explained based on the local narratives of the Yogyakarta jazz community as a mixture of the local and the trans-local scene (Bennett & Peterson 2004). Furthermore, the reflexive strategy will be analysed through the lens of the youth culture perspective specifically as a manifestation of a mixture between post-subculture (Bennett 1999) and subculture (Blackman 2005). In their everyday musical practices, young jazz musicians produce their musical practices fluidly and flexibly as a lifestyle distinction as well as a form of everyday life resistance. In summary, this article shows the complexity of the musical processes of young jazz musicians in contemporary urban space of Yogyakarta, Indonesia.